Pemberdayaan Masyarakat Melalui Pembangunan Wisata Parsariran Kecamatan Batang Toru - Berlin My Anggelita Pramesthi Cahyaningtyas; Kustini Kustini (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The proficiency in the English language has become a crucial factor in facing the competition in the era of globalization. PT Nusantara Infrastructure Tbk, through its Corporate Social Responsibility (CSR) program entitled “Rumah Pintar Nusantara” actively participates in building and shaping the character of elementary, junior, and high school students in Sawah Baru village, Ciputat sub-district, South Tangerang, Indonesia to be globally competitive. The implementation involves the engagement of MSIB interns as mentors in the teaching process. Employing a mentoring approach based on the utilization of songs and ice breaking, it is anticipated that this method creates an enjoyable learning atmosphere for the students. The outcomes of this community engagement demonstrate the students’ high enthusiasm in comprehending the learning materials and achieving a better understanding